Being and Experiencing: Jamasan Tombak Kyai Upas Sebagai Ritual Warisan Mataram Yogyakarta di Kabupaten Tulungagung dalam Perspektif David N. Elkins - Santosa, Bagus; Lestari, Sri; Sulistyo, Hary; Indianto S, Dimas (Humanis, 2024)
This study examines the Jamasan Kyai Upas ritual, a Mataram Yogyakarta heritage still practiced by the Tulungagung community. While traditionally associated with the Yogyakarta Sultanate, the Kyai Upas spear, a symbolic heirloom of Tulungagung, remains a significant cultural element. The study explores the ritual’s historical continuity, its symbolic meaning, and the community’s beliefs surrounding the heirloom. Using a qualitative ethnographic approach, this research employs Elkins’ (1998) theory of spirituality, which emphasizes being and experiencing as awareness of transcendence and core values in life. Data was collected through interviews to link cultural beliefs (being) and experiences (experiencing) with the ritual. Findings reveal that (1) the Kyai Upas spear connects Tulungagung’s identity with the Yogyakarta Sultanate and (2) the spear symbolizes good fortune and safety for the Tulungagung community, grounded in historical and contemporary contexts.